Rituximab efficiently depletes B cells in lung tumors and normal lung tissue [version 1; referees: 2 approved] - Albane Joly-Battaglini; Clara Hammarström; Branislava Stankovic; Henrik Aamodt; Johan Stjärne; Odd Terje Brustugun; Åslaug Helland; Inger Øynebråten; Alexandre Corthay (F1000Research, 2016)
Rituximab is a monoclonal antibody that targets the CD20 B-cell-specific antigen and is widely used as therapy for B-cell lymphoma. Since rituximab depletes both malignant and normal B cells, it is increasingly being used to treat various conditions in which normal B cells have a pathogenic role, such as rheumatoid arthritis and multiple sclerosis. It is well-established that rituximab efficiently eliminates B cells in blood, lymph nodes, and spleen. In contrast, the effect of rituximab in non-lymphoid tissues remains poorly documented and is debated. Here, we report a rheumatoid arthritis patient who was treated with rituximab before receiving thoracic surgery for non-small cell lung cancer. Using flow cytometry and immunohistochemistry, we show that rituximab efficiently depleted CD20-positive B cells in a primary lung tumor, in lung-associated lymph nodes, and in normal lung tissue. We conclude that rituximab may be very efficient at depleting normal B cells in the lungs. This property of rituximab may potentially be exploited for the treatment of conditions in which pathogenic B cells reside in the lungs. On the other hand, the clearance of lung B cells may provide an explanation for the rare cases of severe non-infectious pulmonary toxicity of rituximab.